The Role of Teacher in Dangerous Minds Movie - Bawani, Bawani (LANTERN (Journal on English Language, Culture and Literature), 2013)
This research is about the role of teacher in Dangerous Minds movie. In this study the writer used the library research. It is a study in the library to get relevant data to the topic that will be discussed. In this study, the writer uses two types of research approach. They are Exponential approach and Theories of Pedagogy which is related with the sociological literary approach. Teacher play an important role, especially for her students. In Dangerous Minds movie, which a lot of conflicts, and each characteristics, with these differences, each character interacts with another one. From the interactions, role teacher can be seen.From the discussion, it can be said that in Dangerous Mind movie, Lou Anne Johnson is a teacher that have a unique method to teach her students. This makes her students become closer and closer to her. Her teaching methods are unique and make her student respect her as her behavior. Miss Johnson very important and involved in the role of the teacher, such as direct contact, one-to-one precepting, and role modeling. Three main role of the teacher can played by Ms Johnson well, so her students can make good development in her behavior and scores.